UMAR BIN KHATTAB’S PHILOSOPHICAL IJTIHAD THINKING ON THE RESTORATIVE JUSTICE APPROACH IN ISLAMIC CRIMINAL LAW - Suhartati; Musyahid, Achmad; Sultan, Lomba; Syatar, Abdul (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2024)
This study examined the depth of Caliph Umar bin Khattab’s philosophical thinking in applying ijtihad in the context of Islamic criminal law, especially related to the restorative justice approach. By analyzing various policies and legal decisions taken by Umar, this study attempted to uncover the philosophical basis underlying the application of the principles of restorative justice in the Islamic justice system during his leadership by identifying the values of justice, humanity, and maslahah as the main pillars of Umar bin Khattab’s ijtihad thinking in the context of restorative justice. Using a descriptive qualitative approach, this study examined primary and secondary sources, including fiqh books and modern literature on restorative justice. The results of the study showed that Umar’s ijtihad was not only based on literal Sharia texts but also considered maslahat (benefit) and the social context of society. This could be seen in decisions such as the temporary suspension of the punishment of amputation of hands during a time of famine, which illustrated the law’s flexibility in responding to emergencies.